Α-Coupled Fixed Points and Their Application in Dynamic Programming. (19th August 2014) - Harjani, J.; Rocha, J.; Sadarangani, K.
Abstract : We introduce the definition of α -coupled fixed point in the space of the bounded functions on a set S and we present a result about the existence and uniqueness of such points. Moreover, as an application of our result, we study the problem of existence and uniqueness of solutions for a class of systems of functional equations arising in dynamic programming.